Acute impact of blood flow restriction on strength-endurance performance during the bench press exercise - Gepfert, M.; Jarosz, J.; Wojdala, G.; Krzysztofik, M.; Campos, Y.; Filip-Stachnik, A.; Kostrzewa, M.; Gawel, D.; Szkudlarek, A.; Godlewski, P.; Stastny, P.; Wilk, M. (Biology of Sport, 2021)
The main goal of the present study was to evaluate the acute effects of blood flow restriction (BFR) at 70% of full arterial occlusion pressure on strength-endurance performance during the bench press exercise. The study included 14 strength-trained male subjects (age = 25.6 ± 4.1 years; body mass = 81.7 ± 10.8 kg; bench press 1 repetition maximum (1RM) = 130.0 ± 22.1 kg), experienced in resistance training (3.9 ± 2.4 years). During the experimental sessions in a randomized crossover design, the subjects performed three sets of the bench press at 80% 1RM performed to failure with two different conditions: without BFR (CON); and with BFR (BFR). Friedman`s test showed significant differences between BFR and CON conditions for the number of repetitions performed (p < 0.001); for peak bar velocity (p < 0.001) and for mean bar velocity (p < 0.001). The pairwise comparisons showed a significant decrease for peak bar velocity and mean bar velocity in individual Set 1 for BFR when compared to CON conditions (p = 0.01 for both). The two-way repeated measures ANOVA showed a significant main effect for the time under tension (p = 0.02). A post-hoc comparisons for the main effect showed a significant increase in time under tension for BFR when compared to CON (p = 0.02). The results of the presented study indicate that BFR used during strength-endurance exercise generally does not decrease the level of endurance performance, while it causes a drop in bar velocity